Origin, Analytical Characterization, and Use of Human Odor in Forensics. Issue 2 (25th January 2017) - Cuzuel, Vincent; Cognon, Guillaume; Rivals, Isabelle; Sauleau, Charles; Heulard, François; Thiébaut, Didier; Vial, Jérôme
Abstract: Developing a strategy to characterize the odor prints of individuals should be relevant to support identification obtained using dogs in courts of justice. This article proposes an overview of the techniques used for the forensic profiling of human odor. After reviewing the origin of human odor—both genetic and physiological—the different analytical steps from sample collection to statistical data processing are presented. The first challenge is the collection of odor, whether by direct sampling with polymer patches, cotton gauze, etc., or indirect sampling with devices like Scent Transfer Unit. Then, analytical techniques are presented. Analyses are commonly performed with gas chromatography coupled with mass spectrometry. As they yield large amounts of data, advanced statistical tools are needed to provide efficient and reliable data processing, which is essential to give more probative value to information.